2004
DOI: 10.1093/wjaf/19.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Arboreal Squirrel Response to Silvicultural Treatments for Dwarf Mistletoe Control in Northeastern Oregon

Abstract: Various silvicultural treatments are commonly used to sanitize stands by removing trees infected with dwarf mistletoe (Arceuthobium spp.), yet witches' brooms in trees infected with dwarf mistletoe often provide structures used by many wildlife species. We compared relative abundance, habitat use, and area of use of red squirrels (Tamiasciurus hudsonicus) and northern flying squirrels (Glaucomys sabrinus) before and after two different treatments designed to remove a range of dwarf mistletoe-caused witches' br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Our study and several others (Vahle 1978, Patton and Vahle 1986, Parks et al 1999, Tinnin and Forbes 1999, Bull et al 2004 indicated that small mammals, particularly red squirrels, frequently use brooms for nesting sites and that the characteristics and locations of the brooms used were similar. The small mammal nests we found occurred more often in Type II brooms, but Type I and III brooms were also commonly used.…”
Section: ]supporting
confidence: 73%
See 3 more Smart Citations
“…Our study and several others (Vahle 1978, Patton and Vahle 1986, Parks et al 1999, Tinnin and Forbes 1999, Bull et al 2004 indicated that small mammals, particularly red squirrels, frequently use brooms for nesting sites and that the characteristics and locations of the brooms used were similar. The small mammal nests we found occurred more often in Type II brooms, but Type I and III brooms were also commonly used.…”
Section: ]supporting
confidence: 73%
“…Most red squirrel nests we found in brooms were also located within 3 m of the main bole and between 4.5 m and 10 m above the ground. Tinnin and Forbes (1999) and Bull et al (2004) reported similar nest heights for the red squirrel nests they found in brooms. We also found that large brooms with some type of platform were more frequently used by small mammals for nesting sites than were small brooms.…”
Section: ]mentioning
confidence: 59%
See 2 more Smart Citations
“…Retention of patches that include a mix of conifer species or conifer and deciduous trees and moderate to high basal area could promote nesting opportunities, connectivity for arboreal travel, as well as abundance and diversity of hypogeous fungi (Dodd et al 2003;Lehmkuhl et al 2004Lehmkuhl et al , 2006b. We recommend experimental studies to explore the effect of patch retention on western gray squirrels, including assessment of optimal patch size and efficacy of the treatment for retaining mistletoe structure for wildlife use while protecting the surrounding stand from mistletoe spread and wildfire (Bull et al 2004). To enhance nesting opportunities for western gray squirrels, we recommend retaining trees .20 cm diameter at breast height (min.…”
Section: Management Implicationsmentioning
confidence: 99%